2011
DOI: 10.1001/archdermatol.2011.260
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Imiquimod Cream, 5%, for Lentigo Maligna After Complete Excision

Abstract: Setting: A multidisciplinary melanoma clinic at a major tertiary hospital.Patients: Forty-three patients with biopsy-proven LM of greater than 5 mm in diameter completed this study.Interventions: Imiquimod cream, 5%, was applied to the lesion 5 days a week for 12 weeks. The original lesion was excised with a 5-mm margin. Main Outcome Measures:The primary outcome was histopathologic evidence of LM in the excision specimen assessed independently by 2 of 3 dermatopathologists. Visible inflammation during treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 43 publications
1
43
0
2
Order By: Relevance
“…Some tumors in original studies were not included in the final analysis because of the use of combination therapy (1), 40 because they had been previously published (1), 26 because they had a diagnosis other than LM (1), 44 or because there were dropouts (2). 18,55 The cases spanned from 2000 to 2014, with follow-up time ranging from 0 to 48.6 months. Of 347 included tumors, 110 came from case studies and 237 from cohort studies (including 42 from 1 arm of a randomized controlled trial).…”
Section: Resultsmentioning
confidence: 99%
“…Some tumors in original studies were not included in the final analysis because of the use of combination therapy (1), 40 because they had been previously published (1), 26 because they had a diagnosis other than LM (1), 44 or because there were dropouts (2). 18,55 The cases spanned from 2000 to 2014, with follow-up time ranging from 0 to 48.6 months. Of 347 included tumors, 110 came from case studies and 237 from cohort studies (including 42 from 1 arm of a randomized controlled trial).…”
Section: Resultsmentioning
confidence: 99%
“…This treatment has been recently reported as a potentially effective second-line treatment for LM, however, evidence for this treatment is still in preliminary stages. Typical regimens range from three-times weekly treatment to daily treatment for 2 weeks to 7 months [58][59][60]. A brisk inflammatory reaction is often seen and is desired as this is thought to correspond with immunologic response [61].…”
Section: • • Medical Managementmentioning
confidence: 99%
“…An interventional study by Ly et al in which imiquimod 5% cream was applied five-times weekly for 12 weeks followed by excision demonstrated histopathologic clearance in 53% of patients, with poor concordance between macroscopic and histopathologic clearance [59]. However, a review article including 264 patients treated with various regimens reported 82% clinical or histologic clearance.…”
Section: • • Medical Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Robust inflammation at imiquimod-treated sites has been reported as a possible prognostic factor of improved response for LM. 10,13 Our study aimed to determine the long-term effectiveness of imiquimod as primary or adjuvant treatment of LM and to examine the differences and potential significance of the inflammatory reaction in a retrospectively identified cohort of patients.…”
mentioning
confidence: 99%